Profitability and adoption of limit feeding during the stocker phase - Hissong, Claudia (Kansas State University, 2021)
This analysis aims to measure and quantify the profitability and adoption of limit feeding stocker cattle to better assist producers with management decisions. One analysis looks at comparing the profitability of limit feeding or ad libitum feeding stocker cattle, and the other looks at factors that influence producer adoption of limit feeding. When comparing the profitability of limit feeding and ad libitum feeding, values of interest were measured at the stocker phase, feedlot phase, and at harvest. At the stocker phase, cattle performance, feed costs, labor requirements, and machinery usage costs were collected. Cost of gain and performance was measured throughout the feedlot phase, and then quality grades, yield grades, and dressing percentages were recorded at harvest. These values allowed for producer budget sheets to be constructed that compare the profitability of limit feeding or ad libitum feeding stocker cattle or compare the profitability of finishing cattle that had been limit fed or fed ad libitum during the stocker phase. During the research trial a net benefit was observed for limit feeding stocker cattle, but it was more profitable to finish cattle that had been fed ad libitum at the stocker phase. However, much of this profitability relies on input costs and rate of adoption within the industry. To analyze the factors that influence producer’s adoption of limit feeding, willingness to change between practices, and measure producer’s views of different management options, a producer survey was conducted. Stocker producers were asked to complete a survey that included questions regarding operator characteristics, operational characteristics, respondents’ preferences, and a choice experiment. Results from producers that currently limit feed showed that main socioeconomic variables do not influence a producer’s decision to limit feed. Within the choice experiment, producers that currently limit feed are more likely to select limit feeding, producers that have a bachelor’s degree and above are more likely to select ad libitum feeding, and producer’s that sell 50% or more of their cattle through a traditional auction market are more likely to select ad libitum feeding. Additionally, if producers see an increase in ADG or a cost benefit the probability of them switching to limit feeding increases. Results from this survey provide a better understanding of potential adoption of limit feeding, measure market impacts that may occur, and target educational programs that are most beneficial to producers.
Keywords: Limit feeding; Economics; Stocker cattle